A new neotropical predaceous midge, Downeshelea deanei, and redescription of Downeshelea guianae (Wirth)(Diptera: Ceratopogonidae) - Maria Felippe-Bauer; Adília R. Quintelas; Gustavo R. Spinelli (Memorias do Instituto Oswaldo Cruz, 1995)
A new species of Downeshelea Wirth & Grogan, D. deanei Felippe-Bauer & Quintelas, is described and illustrated from a male specimen from Trinidad, and a redescription of D. guianae (Wirth) is given.